2021
DOI: 10.1111/dth.14773
|View full text |Cite
|
Sign up to set email alerts
|

Proposition of a severity scale for lichen sclerosus: The “Clinical Lichen Sclerosus Score”

Abstract: Vulvar lichen sclerosus (VLS) is a chronic inflammatory skin disease of the anogenitalarea leading to itch, burning, sexual dysfunction and impaired quality of life. An unmet need in the context of LS is a practical, easily assessable grading scale to classify disease severity and to allow intra-and interindividual comparisons. The objectives of this study were i) to assess the prevalence and severity of 23 items proposed by a recent Delphi consensus group in patients with adult VLS. ii) to develop a clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…One of the most prominent symptoms of VLS is pruritus, which was also the most common symptom reported in our study [1]. In a study of 143 patients with VLS, 90% were symptomatic, with 37% reporting dyspareunia and changes in sexual function [5]. Some impact on sexual function was reported in 42% of the current sample.…”
Section: Discussionmentioning
confidence: 53%
“…One of the most prominent symptoms of VLS is pruritus, which was also the most common symptom reported in our study [1]. In a study of 143 patients with VLS, 90% were symptomatic, with 37% reporting dyspareunia and changes in sexual function [5]. Some impact on sexual function was reported in 42% of the current sample.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have not demonstrated a correlation between symptom severity and macroscopic anatomic changes. 6,15 Our finding here of an association between symptom severity and microscopic histopathologic changes should be investigated in a larger study. Study limitations include sample size, inclusion of patients from a single academic medical center, and consistent biopsy sampling of the same anatomic site rather than the most symptomatic site.…”
Section: Discussionmentioning
confidence: 73%
“…Although ulceration and erosion were included in the original ISSVD Delphi consensus, these signs were excluded in the final version of the CLISSCO scoring system based on this consensus. 6,7 Future iterations of VLS severity scores should consider the inclusion of these signs. Finally, those 4 patients with a severe VQLI score had trends for higher average thickness of the stratum corneum, other epidermal layers, and dermal sclerosis than those 2 patients with mild VQLI scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations